Cultural heritage information access and management - Ruthven, Ian 1968-; Chowdhury, G. G. (Gobinda G.) (London Facet Publishing, 2015)
Currently, the Internet and digitization have offered new opportunities for providing better and wider access, but they also pose new challenges. This collection of essays addresses accessing and managing cultural heritage information resources.
Managing digital cultural heritage information / Gobinda Chowdhury and Ian Ruthven -- Digital humanities and digital cultural heritage (alt-history and future directions) / Chris Alen Sula -- Management of cultural heritage information : policies and practices / Gobinda Chowdhury -- Cultural heritage information : artefacts and digitization technologies / Melissa Terras -- Metadata in cultural contexts : from manga to digital archives in a linked open data environment / Shigeo Sugimoto, Mitsuharu Nagamori, Tetsuya Mihara, and Tsunagu Honma -- Managing cultural heritage : information systems architecture / Lighton Phiri and Hussein Suleman -- Cultural heritage information users and usability / Sudatta Chowdhury -- A framework for classifying and comparing interactions in cultural heritage information systems / Juliane Stiller and Vivien Petras -- Semantic access and exploration in cultural heritage digital libraries / Ali Shiri -- Supporting exploration and use of digital cultural heritage materials : the PATHS perspective / Paul Clough, Paula Goodale, Mark Hall and Mark Stevenson -- Cultural heritage information services : sustainability issues / Gobinda Chowdhury.
"First published in the United Kingdom by Facet Publishing, 2015"--Title page verso.
Includes bibliographical references and index.
Keywords: Digital preservation; Library materials -- Digitization; Archival materials -- Digitization; Cultural property -- Digitization; Information technology -- Social aspects; User interfaces (Computer systems) -- Design; Metadata